Production of Submicroparticles of β-Sitosterol Using an Aerosol Solvent Extraction System - 于文利 夏菲 金鹤阳 林长春 赵亚平 蒋思源 何琳 (Chinese journal of chemical engineering, 2008)
The submicroparticles of β-sitosterol were produced by using an aerosol solvent extraction system （ASES） and characterized by scanning electronic microscope （SEM）, X-ray diffraction （XRD）, and Fourier transform infrared （FT-IR） analysis. The effects of operational parameters including pressure, temperature, solution concentration, and ratio of flow rate （CO2/solution, r） on particle size （PS）, yield, and morphology were investigated. The results showed that microparticles of β-sitosterol （less than 1000 nm size and larger than 70% yield） could be obtained at 10-15 MPa, 35 50℃, 15 mg·ml^-1, 10/1（r）; β-sitosterol particles were found to occur as three mophologies： flakes, rods, and spheres by varying ratio of flow rate or solution concentration. In contrast, the crystallinity of β-sitosterol decreased, whereas its molecular structure remained almost unchanged after being ASES-treated. Therefore, ASES was an effective method to produce submicroparticles of β-sitosterol.